Efektifitas Pembelajaran dalam Pengembangan Bakat dan Minat Peserta Didik - Neliwati; Adolina; Al-Faris, Rizza Fikri; Aisyah, Siti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In essence, students' talents, abilities and capacities need to be developed and trained in order to produce the desired results, including talented students. The aim of this research is to analyze Class Teacher Strategies in Developing Students' Talents and Interests at MIN 5 Labuhanbatu. This type of research is qualitative research by developing concepts based on inductive data and collecting data and being scientific in nature. The data collection techniques used were observation, interviews and documentation. Data analysis is carried out by organizing data, describing it into units, synthesizing it, arranging it into patterns, choosing what is important and what will be studied and making conclusions. The results of this research are that support, direction, motivation from parents and educators, availability of facilities and infrastructure, as well as the use of digital media such as Power Point and YouTube, are the keys to developing the talents and interests of students at MIN 5 Labuhanbatu.